2022
DOI: 10.1038/s41598-022-24338-8
|View full text |Cite
|
Sign up to set email alerts
|

Preterm toddlers have low nighttime sleep quality and high daytime activity

Abstract: A number of studies have been made on the sleep characteristics of children born preterm in an attempt to develop methods to address the sleep problems commonly observed among such children. However, the reported sleep characteristics from these studies vary depending on the observation methods used, i.e., actigraphy, polysomnography and questionnaire. In the current study, to obtain reliable data on the sleep characteristics of preterm-born children, we investigated the difference in sleep properties between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similarly, Asaka et al 35 found in Japan through actigraphy that preterm toddlers had lower sleep quality compared to term toddlers, with more nocturnal awakenings and higher wakefulness after sleep onset (WASO). Preterm toddlers also had higher daytime activity, which may be associated with poor attention and hyperactivity at school age 35 . A frequent question in premature infants with bronchopulmonary dysplasia (BPD) discharged from the neonatal intensive care unit (NICU) on home oxygen therapy is the safety and timeframe for discontinuation in a secure and stress‐free manner.…”
Section: Sleep and Prematuritymentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, Asaka et al 35 found in Japan through actigraphy that preterm toddlers had lower sleep quality compared to term toddlers, with more nocturnal awakenings and higher wakefulness after sleep onset (WASO). Preterm toddlers also had higher daytime activity, which may be associated with poor attention and hyperactivity at school age 35 . A frequent question in premature infants with bronchopulmonary dysplasia (BPD) discharged from the neonatal intensive care unit (NICU) on home oxygen therapy is the safety and timeframe for discontinuation in a secure and stress‐free manner.…”
Section: Sleep and Prematuritymentioning
confidence: 95%
“…Howarth et al 34 found among a cohort of 172 patients <18 years where 19 were classified as Low Birth Weight, that the latter was associated with increased sleep disruption and sleep efficiency <80%, and a higher likelihood of OSA. Similarly, Asaka et al 35 found in Japan through actigraphy that preterm toddlers had lower sleep quality compared to term toddlers, with more nocturnal awakenings and higher wakefulness after sleep onset (WASO). Preterm toddlers also had higher daytime activity, which may be associated with poor attention and hyperactivity at school age 35 .…”
Section: Sleep and Prematuritymentioning
confidence: 95%
See 1 more Smart Citation